178 High Abbreviated Injury Scale Grade Conversion Rate Following Neuro-Spinal Scaffold Implantation in Acute Thoracic Complete Abbreviated Injury Scale A Spinal Cord Injury: Potential Mechanisms. (August 2016) - Theodore, Nicholas; Kim, Kee Duk; Hsieh, Patrick C.; Ray, Wilson Zachary; Barry, Maureen; Layer, Rick; Moore, Simon W.; Coric, Domagoj
Abstract : INTRODUCTION: In preclinical models, Neuro-Spinal Scaffold (NSS) implantation following spinal cord injury (SCI) promotes neural sparing and regeneration through internal decompression and tissue remodeling. Rather than typical postinjury cyst formation, the NSS acts through appositional healing to form neuropermissive remodeled tissue. A pilot study of the NSS enrolled 5 patients with complete thoracic SCI; 3 converted to incomplete. Neurological recovery in 2 patients was either sustained (beyond 12 months) or delayed by 6 months. Postinjury MRI scans and clinical time course suggest that reduced cyst formation and ongoing neural regeneration may contribute to these observations. METHODS: Scaffolds were implanted 7 to 81 hours after injury within the intraspinal lesion. ISNCSCI examinations and MRIs were performed before implantation and through 6-month follow-up. RESULTS: There were no NSS-related serious safety events. On screening MRI, patients typically exhibited spinal cord compression and edema. Three of 5 patients had intraspinal hemorrhage. Based on central neuroradiology review of pre- and postoperative MRI scans through 6 months, none of the patients had definite cyst formation defined by T2 and T1 changes. By 6 months, 3 of 5 patients had converted from Abbreviated Injury Scale (AIS) A to AIS B(2) or C(1). One patient gained 10 points of hip and knee function by 6 months, with additional improvement and new ankle function at 12 months (increased motor score of 8). One patient converted from AIS A to B at 6 months, a late-occurring conversion that is extremely rare. CONCLUSION: This study represents the first use of the intraspinal NSS in patients with complete thoracic SCI. By 6 months, the low incidence of cyst formation with preservation of some intralesion internal architecture is consistent with preclinical results in which the resorbable NSS was replaced by a matrix of axon-containing remodeled tissue. The possibility of ongoing neural regeneration may contribute to the high incidence of AIS conversion and sustained period of neurological recovery.